INTREPID II: protocol for a multistudy programme of research on untreated psychosis in India, Nigeria and Trinidad. Issue 6 (21st June 2020) - Roberts, Tessa; Gureje, Oye; Thara, Rangaswamy; Hutchinson, Gerard; Cohen, Alex; Weiss, Helen Anne; John, Sujit; Lee Pow, Joni; Donald, Casswina; Olley, Bola; Miguel Esponda, Georgina; Murray, Robin M; et al.
Abstract : Introduction: There are few robust and directly comparable studies of the epidemiology of psychotic disorders in the Global South. INTREPID II is designed to investigate variations in untreated psychotic disorders in the Global South in (1) incidence and presentation (2) 2-year course and outcome, (3) help-seeking and impact, and (4) physical health. Methods: INTREPID II is a programme of research incorporating incidence, case–control and cohort studies of psychoses in contiguous urban and rural areas in India, Nigeria and Trinidad. In each country, the target samples are 240 untreated cases with a psychotic disorder, 240 age-matched, sex-matched and neighbourhood-matched controls, and 240 relatives or caregivers. Participants will be followed, in the first instance, for 2 years. In each setting, we have developed and are employing comprehensive case-finding methods to ensure cohorts are representative of the target populations. Using methods developed during pilot work, extensive data are being collected at baseline and 2-year follow-up across several domains: clinical, social, help-seeking and impact, and biological. Ethics and dissemination: Informed consent is sought, and participants are free to withdraw from the study at any time. Participants are referred to mental health services if not already in contact with these and emergency treatment arranged where necessary. All data collected are confidential, except when a participant presents a serious risk to either themselves or others. This programme has been approved by ethical review boards at all participating centres. Findings will be disseminated through international conferences, publications in international journals, and through local events for key stakeholders.